The Nature of the Universe in Al-Kindi's Metaphysical Perspective and Its Coherence with Qur'anic Evidence - El Yasmin, Yusroh; Khudori Soleh, Achmad (Jurusan Aqidah dan Filsafat Islam Universitas Negri Sunan Gunung Djati Bandung, 2024)
The form of the universe can be seen by the five senses, but the nature of the creation of the universe is included in the study area of metaphysics because it is abstract and related to the nature of God's form. In the study of philosophy, the nature of the universe is still widely debated; however, these differences are based on the arguments of the thoughts of each philosopher. One of the philosophers who expressed his opinions about the nature of the universe was A-Kindi. This article aims to reveal the nature of the universe from the metaphysical perspective of Al-Kindi, who was one of the Muslim philosophers and the first Arab to introduce philosophy to Islam. This study used a qualitative research method based on the type of library research. The researcher used book literature and previous research journals as a source of data. Furthermore, the researcher analyzed and described the data in a narrative manner. The results of this study reveal that Al-Kindi's metaphysical perspective on the universe is muhdats (new), which means that the universe is a creature (created) not derived from the emnation of the form of the date (God). Al-Kindi's opinion on the creation of the world can be coherent with the verses of the Qur'an: QS. Al-Hadid (57): 3, QS. Hud (11): 7, QS. Al-Anbiya' (21): 30, QS. Al-Baqarah (2): 117.